The Role of Discretion in Handling COVID-19 - Alvian Rachmad Eko Purnomo; Didik G. Suharto; Rutiana D. Wahyunengseh (Department of State Administration - Musamus University, 2020)
Indonesia is now experiencing national disaster called covid-19 or corona outbreak. This case will be a kind of history in the future to become a lesson for central or regional government in making public policy in emergency state. By facing the covid-19 outbreak, public officials must quickly resolve the problem. Discretion gives the opportunity for public officials to do free action to solve the urgent case. Public officials are given alternatives to reach the aim of public service by using discretion even though there is no regulation upon it. Moreover, we know that the implementation of discretion still remains several problems. This research used the literature study method with a qualitative research approach. It was based on several references in order to give the description of the discretion role in handling covid-19 outbreak. Theoretical reference in discussing discretion role was based on the study of journals, books, dan others. Being deeply studied, the discretion implementation of social distancing in big scale belongs to regulatory policy that needs social planning discretion. This type creates more different interests and contains a relatively high complexity. The result of study shows that the implementation of discretion is important because the main function of government is to serve the citizens in emergency state. Therefore, discretion becomes the effective and efficient choice. The integrity of discretion makers becomes one of the variable indicators in creating successful discretion. The government accountability needs to be explained to the society. Moreover, it can be studied more fairly.